2011
DOI: 10.1016/j.expneurol.2010.12.017
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal behavioral, cross-sectional transcriptional and histopathological characterization of a knock-in mouse model of Huntington's disease with 140 CAG repeats

Abstract: The discovery of the gene mutation responsible for Huntington's Disease (HD), huntingtin, in 1993 allowed for a better understanding of the pathology of the and enabled development of animal models. HD is caused by the expansion of a polyglutamine repeat region in the N-terminal of the huntingtin protein. Here we examine the behavioral, transcriptional, histopathological and anatomical characteristics of a knock-in HD mouse model with a 140 polyglutamine expansion in the huntingtin protein. This CAG 140 model … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
41
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(45 citation statements)
references
References 95 publications
4
41
0
Order By: Relevance
“…D2GFP decline progresses through 31 wk of age before plateauing at ∼62% of wild type. This D2GFP loss is before the reported rotarod latency deficit, and is also before the age at which reliable detection of Drd2 loss by in situ hybridization is reported (27). Before plateauing, this strain demonstrates greater variance at the younger ages tested.…”
Section: D2gfp Loss Is Progressive In Both Fragment and Full-length Hdmentioning
confidence: 60%
“…D2GFP decline progresses through 31 wk of age before plateauing at ∼62% of wild type. This D2GFP loss is before the reported rotarod latency deficit, and is also before the age at which reliable detection of Drd2 loss by in situ hybridization is reported (27). Before plateauing, this strain demonstrates greater variance at the younger ages tested.…”
Section: D2gfp Loss Is Progressive In Both Fragment and Full-length Hdmentioning
confidence: 60%
“…By contrast to florid mouse models carrying an N-terminal huntingtin fragment (e.g., R6/2 mice), mice carrying a chimeric mouse/human exon 1 containing 140 CAG repeats inserted in the murine huntingtin gene more faithfully model the disease genetics and have normal life spans (26,27), and they develop a subtle pathologic phenotype that is most analogous to presymptomatic and early symptomatic stages of the human disease (26). Despite a mild phenotype, knock-in mice have abnormal motor behavior that can be quantified by formal behavioral testing and aged mice show characteristic striatal nuclear huntingtin aggregates (26,27) as well as ∼20% underexpression of select striatal enriched transcripts [e.g., D2 receptor and dopamine-and cAMP-regulated neuronal phosphoprotein (DARPP-32)] (27) in the absence of neuronal cell loss.…”
Section: Expression Of the H2afy-encoded Protein Macroh2a1 Is Increasmentioning
confidence: 99%
“…Despite a mild phenotype, knock-in mice have abnormal motor behavior that can be quantified by formal behavioral testing and aged mice show characteristic striatal nuclear huntingtin aggregates (26,27) as well as ∼20% underexpression of select striatal enriched transcripts [e.g., D2 receptor and dopamine-and cAMP-regulated neuronal phosphoprotein (DARPP-32)] (27) in the absence of neuronal cell loss. To validate our findings in this full-length huntingtin knock-in model, we assayed macroH2A1 levels in histone extracts from the striatum of homozygous 140-CAG knock-in mice compared with age-and sex-matched wildtype mice.…”
Section: Expression Of the H2afy-encoded Protein Macroh2a1 Is Increasmentioning
confidence: 99%
“…PDE10A is therefore an attractive target for novel therapies for a variety of neurologic and psychiatric disorders that involve striatal function (9), including Parkinson disease (10), Huntington disease (11,12), schizophrenia (13,14), memory disorders (15), depression, and addiction (16). Animal models of Huntington disease have shown that PDE10A expression is an extremely sensitive marker of striatal neuron loss (12,17), and Parkinson disease models have been used to demonstrate possible roles of PDE10A in both the early motor symptoms and the late complications of Parkinson disease due to prominent PDE10A-dependent dysregulation of corticostriatal signaling (10,18). Developing imaging agents to accurately and sensitively interrogate PDE10A in vivo would greatly help in understanding changes in PDE10A in human brain disorders and speed the development of potential therapeutics targeting this enzyme.…”
mentioning
confidence: 99%